Identifying the HLA DRB1-DQB1 molecules and predicting epitopes associated with high-risk HPV infection clearance and redetection. (2020)
Several determining factors are involved in HPV infection outcomes; human leukocyte antigen (HLA) polymorphisms have been described as related factors. This study has ascertained the effect of genetic variation on HLA-DRB1 and DQB1 genes on HPV-16/-18/-31/-33/-45 and -58 clearance and redetection in Colombian women. PCR and qPCR were used for viral identification and the Illumina MiSeq system was used for HLA-typing of cervical samples (n=276). Survival models were adjusted for identifying alleles/haplotypes related to HPV clearance/redetection; L1/L2 protein-epitope binding to MHC-II molecules was also predicted. Significant associations suggested effects favouring or hampering clearance/redetection events depending on the viral type involved in infection, e.g. just DRB1*12:01:01G favoured HPV-16 (coeff: 4.8) and HPV-45 clearance (coeff: 12.65) whilst HPV-18 (coeff: 2E-15), HPV-31 (coeff: 8E-17) and HPV-58 hindered elimination (coeff: 1E-14). An effect was only observed for some alelles when configured as haplotypes, e.g. DRB1*04:07:01G (having the greatest frequency in the target population) was associated with DQB1*02:01:1G or *03:02:03. Epitope prediction identified 23 clearance-related peptides and 29 were redetection-related; eight might have been related to HPV-16/-18 and -58 persistence and one to HPV-18 elimination. HLA allele/haplotype relationship with the course of HPV infection (clearance/redetection) depended on the infecting HPV type, in line with the specific viral epitopes displayed.